2020
DOI: 10.1109/tifs.2020.2976559
|View full text |Cite
|
Sign up to set email alerts
|

On the Dissection of Evasive Malware

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 46 publications
(72 reference statements)
0
36
0
Order By: Relevance
“…However, this method does not intercept low-level system interactions, such as system calls and x86 instruction, because the bare-metal setup can only reason about raw disk content. A more recent solution is to execute the malicious samples inside a Dynamic Binary Instrumentation (DBI) framework that hides the presence of the analysis environment, identifying anti-instrumentation techniques [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method does not intercept low-level system interactions, such as system calls and x86 instruction, because the bare-metal setup can only reason about raw disk content. A more recent solution is to execute the malicious samples inside a Dynamic Binary Instrumentation (DBI) framework that hides the presence of the analysis environment, identifying anti-instrumentation techniques [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose an anti-anti-VM study to complement the limitations of the technique suggested by Cheng, Binlin, et al Therefore, if the above study were to consider the results of this paper, analysis may be conducted in a safer environment. D'Elia, Daniele Cono, et al [13] proposed Bluepill, a human-centered dynamic analysis system to facilitate malware analysis. Bluepill is based on DBI tool, and the authors of the above mentioned study configured a rule set for automatic bypass by analyzing known anti-analysis techniques.…”
Section: Related Workmentioning
confidence: 99%
“…response [9], [10]. Network forensics collects and analyzes data related to computer networks [11], which mainly refers to digital forensics that analyzes and monitors network connection information or packets.…”
Section: Introductionmentioning
confidence: 99%